The architect’s material palette - Buinov, Alexei; Lidin, Konstantin (project baikal, 2023)
During the twentieth century, reinforced concrete acquired a status of a leading building material. Its wide application influenced the construction technologies and the layout of cities and largely shaped the aesthetics of modernism. At the beginning of this century, the cost of cement and concrete production is showing rapid growth, and the environmental burden from cement production is becoming increasingly unacceptable. Economic and environmental factors force us to look for a replacement for reinforced concrete. In particular, there is renewed interest in wood-based building materials. The problem is that the dominance of concrete has formed a stable orientation of architects to a specific set of properties – isotropy, high density, fire safety, and so on, which are absent from wood. A compromise option is cross-laminated timber (CLT), which at the same time has its own disadvantages and limitations. The article concludes that it is necessary to diversify the palette of building materials and develop special training programs for architects to work with a wide range of building materials.